STRENGTHENING THE ROLE OF INDONESIAN STAKEHOLDERS IN ENERGY INCENTIVE: A COMPARATIVE STUDY WITH UK LAW - Dewi Elvani Lumban Gaol; Aprilia Eukarista Paskaria; Lusia Marselina Mbu Pake; Ulya Yasmine Prisandani (Faculty of Law Atma Jaya Yogyakarta University, 2026)
The recent geopolitical tensions in the Middle East have created negative sentiment on oil prices. Indonesia has also been affected as a country that is still quite dependent on oil imports. Although several types of incentives in the RE sector have been implemented in Indonesia over the past few decades their implementation is still not optimal. This paper aims to examine the roles and responsibilities of Indonesian government stakeholders in the formulation, implementation, and oversight of energy-incentive regulations, and to identify UK regulatory best practices that can be adapted to strengthen stakeholder capacity, coordination, and accountability in Indonesia. This research uses normative legal methods with Indonesian and UK legislation as primary sources, supported by journals, reports, and government publications to compare stakeholder involvement in optimizing energy incentives. The best aspect that could be adopted by Indonesia from UK is the establishment of an independent energy regulator. This body is expected to streamline incentive schemes, reduce bureaucratic barriers, and foster investor confidence by integrating consultation, coordination, oversight, and digital transparency.